The Influence of Different Target Values and Measurement Times on the Decreasing Force Curve during Sustained Static Gripping Work - Nakada, Masakatsu; Yamaji, Shunsuke; Demura, Shinichi; Nagasawa, Yoshinori (Journal of PHYSIOLOGICAL ANTHROPOLOGY, 2006)
The purposes of this study were to clarify the decreasing properties of, and to examine useful measurement times for evaluating muscle endurance in a comparison among various parameters using measurement times of 1, 3 and 6 mins and target values of 50, 75 and 100% MVC. Fifteen males and 15 females participated in this study. All subjects carried out sustained isometric gripping under nine conditions of measurement times and target forces, (1, 3 and 6 mins vs. 50, 75 and 100% MVC) with an interval of one or two days. The property of decreasing force in the initial phase (marked decreasing phase) differed among the target values, and the decreasing speed of the gripping force was highest for 100% MVC. However, the decreasing property after about 60 sec, in which the force decreased to about 30% MVC from the onset of grip, was similar among all target values, and then the gripping force reached an almost steady state phase at about 150–180 sec. In other words, the difference of the decreasing property during the initial phase with different target values was considered not to influence the property in the later phase, in which the force decreases to about 30% MVC. When muscle endurance is evaluated from the phase until reaching the steady state, it may be possible to evaluate the same property of the decreasing phase at 6 min as the measurement at 3 min. The measurement for 1 min at 50% MVC was not valid as an evaluation time because the grip force did not decrease enough. The integrated area in the initial phase was considered to depend on the magnitude of the target value, and the integrated area for 30 sec or 60 sec at 75% MVC was larger than that at 100% MVC. It was inferred that higher pain at 100% MVC resulted in a greater decrease in the speed of the force.